ALAT ELEKTROPLATING BERBASIS PENGATUR WAKTU UNTUK PELAPISAN CHROME DI LABORATORIUM PELAPISAN LOGAM - Langgeng, Langgeng; Pratama, Hendra Saputra; Sodiwiryo, Kusetyono Lamiran (Universitas Negeri Surabaya, 2024)
Practicum is a fairly complex teaching and learning process, but the level of complexity is always in line with human development. It is necessary to have facilities or media that can stimulate the learning process so that it runs effectively and efficiently, including tools that support practicum activities. The steel used is usually a type of low carbon steel which is corrosive in air, water and soil. This corrosion can occur because steel throws away electrons, causing the steel to oxidize. Steel that experiences oxidation can become brittle, weak, and unable to bear the load that a steel structure should support. Therefore, corrosion can reduce the durability of low-carbon steel structures as well as pipes. However, with the coating method, low carbon steel can be protected from corrosion. Coating steel using metal can be done using various methods, including electroplating (cold dipping) using the direct current method. The working principle is almost the same as electrolysis, where the galvanized metal acts as the anode, while the base metal specimen acts as the cathode. Apart from prioritizing visual results, other factors are equally important and need to be considered, such as durability and protection from corrosion. Because in certain situations, the metal's resistance to corrosion is very important. This coating refers to surface coating, which is a process of modifying the surface of a material with the aim of obtaining properties such as corrosion resistance, high hardness, high temperature resistance and wear resistance without any significant changes to the structural properties.